Work-family conflict, job satisfaction, and relationship quality among APJII ISP employees in Cilegon - Rahma, Nida Nayla; Emilisa, Netania; Rosalinda, Ana; Saputra, Gavrila Indra; Hannan, Muhammad Syarifin (Socio Politica : Jurnal Ilmiah Jurusan Sosiologi, 2025)
This study examines how Work-to-Family Conflict and Family-to-Work Conflict affect High Quality Relationships among employees of APJII-affiliated Internet Service Providers in Cilegon, with Job Satisfaction as a mediator. Using questionnaires from 150 respondents and SEM analysis, results show both types of conflict are perceived as low, while Job Satisfaction and High Quality Relationships are rated positively. Work-to-Family Conflict negatively impacts both Job Satisfaction and High Quality Relationships, with Job Satisfaction fully mediating this relationship. Family-to-Work Conflict does not significantly affect Job Satisfaction or High Quality Relationships. The findings highlight the need for supportive work policies to enhance job satisfaction and workplace relationships, and suggest expanding future research to include broader variables and contexts. Contribution: The findings provide valuable insights for managers to develop supportive work policies that foster job satisfaction and strong interpersonal relationships, and offer a foundation for future research to explore these dynamics across broader contexts and variables.